2013
DOI: 10.1111/cobi.12218
|View full text |Cite
|
Sign up to set email alerts
|

Factors Mediating Co‐Occurrence of an Economically Valuable Introduced Fish and Its Native Frog Prey

Abstract: Habitat characteristics mediate predator-prey coexistence in many ecological systems but are seldom considered in species introductions. When economically important introduced predators are stocked despite known negative impacts on native species, understanding the role of refuges, landscape configurations, and community interactions can inform habitat management plans. We measured these factors in basins with introduced trout (Salmonidae) and the Cascades frog (Rana cascadae) to determine, which are responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In contrast to the mitigating effect of habitat complexity on multitrophic interactions within habitats (Hartman et al. ), increasing landscape complexity is expected to reinforce multitrophic interactions between habitats by creating edge habitat, potentially completely excluding mesopredators from suitable habitats.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the mitigating effect of habitat complexity on multitrophic interactions within habitats (Hartman et al. ), increasing landscape complexity is expected to reinforce multitrophic interactions between habitats by creating edge habitat, potentially completely excluding mesopredators from suitable habitats.…”
Section: Discussionmentioning
confidence: 98%
“…Within‐pond physical heterogeneity and vegetation structure can increase availability of refugia from predators and diffuse competition (Hartman et al. , Anderson and Semlitsch , Kenison et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, native-invasive interactions can be intensified or mediated by local and landscape habitat characteristics including climate (Melbourne et al 2007. Within-pond physical heterogeneity and vegetation structure can increase availability of refugia from predators and diffuse competition (Hartman et al 2014, Anderson and Semlitsch 2016, Kenison et al 2016. Dominant plant species, such as invasive reed canarygrass (Phalaris arundinacea), can affect both native and invasive amphibians by modifying wetland structure and function, prey resources, and water chemistry (Spyreas et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A tadpole caging experiment with Sierra Nevada yellow-legged frogs (R. sierrae) confirmed that predation of larvae is an important mechanism for the negative effect of trout on frogs (Vredenburg 2004). Notably, the presence of physical refugia from predation (shallow littoral zones and emergent vegetation) is associated with Cascades frog persistence in lakes occupied by introduced trout (Hartman et al 2014). Not all amphibian species are susceptible to predation by trout.…”
Section: Amphibiansmentioning
confidence: 91%